The organization of Philippine vocal and instrumental scores in selected academic music libraries in Metro Manila a survey - Baradas, Josephine Cecilia L. (2000)
The purpose of this study was to determine the following : types of format of Philippine vocal and instrumental music scores that are cataloged in six music libraries in Metro Manila, namely: PWU, SIC, SPCM, SSC, UST, and UPCM; levels of bibliographic description utilized for these scores; sufficiency of the subject authority lists for subject heading assignment for Philippine music scores; provision of additional subject headings; and classification systems adopted for these scores. The music scores analyzed were the published and unpublished Philippine vocal and instrumental music scores composed during the early nineteenth century to the present. This study used the descriptive survey method consisting of questionnaires and interviews.